MATHEMATICS LEARNING DESIGN BASED ON LOCAL WISDOM OF BUTON ETHNOMATHEMATICS IN ELEMENTARY SCHOOLS - Dina Firliana Nurddin; Sitti Hermayanti Kaif; Kiki Fatmala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to design an ethnomathematics-based mathematics learning design that integrates Buton local wisdom into the learning process in elementary schools. This type of research is Research and Development (R&D). The subjects in this study were fourth-grade elementary school students and class teachers involved in the mathematics learning process. This research was carried out through two main stages, namely the exploration stage and the implementation stage of the learning design. Data collection was carried out through observation, interviews, and questionnaires. The results of the study indicate that the integration of the local wisdom of the Buton Palace Fortress in geometry learning has a positive contribution to students' understanding of mathematical concepts. This approach not only helps students understand geometry concepts more concretely but also strengthens their awareness of local cultural values ​​​​that exist in the community.